Social capital in agricultural community development: a review - Ibrahim, Muhammad Bello; Hassan, Salim; Sanyang, Demba (International Organization of Scientific Research, 2017)
Social capital has been focus of interest in considerable social science academic circles in recent years. Development of communities is a continuous process in order to sustain communities through utilizing their assets in a world that is increasingly becoming unpredictable and difficult in terms of togetherness and caring concerns for sustainability. The paper looked first at rural communities and the way social capital is built and utilized positively for community development despite lots of challenges. Social capital in agriculture was reviewed from rural community perspectives and seen as a motivating and gluing force for communitarian work that benefits the agriculture. The development of social capital as unseen capital in any society will provide the community members the force to forge ahead in whatever self-help endeavor their community resolved to undertake. The paper also considers the other side of the coin and looked at marginal community members that did not subscribe to social capital and became excluded from the beneficial collective actions of the majority. The paper lastly, posits that social capital in agricultural communities will go a long way in empowering community members to sustainably produce food and develop their communities.